Revisiting the city augmented by digital technologies – SeeARch tool - Raposo, M.; Eloy, S.; Dias, M. S.; Lopes, M. (Proceedings of the 3rd International Conference on Preservation, Maintenace, and Rehabilitation of Historical Buildings and Structures, 2017)
This paper presents a digital tool that enables the city inhabitants or visitors to acquire in real time, relevant information about several aspects of a given city, augmenting their real experience of the place. We used digital technologies, particularly an in-house developed Augmented Reality (AR) tool referred to as SeeARch,that augments in situ the city explo-ration experience. This tablet-based AR tool, enables mobile users to recognize the facade of specific buildings and, in real-time, superimpose relevant associated 3D and multimedia information, while visiting the city. The aim of this app is to provide customized infor-mation to visitors suiting their own interests and time to visit the city. User satisfaction evaluation tests were performed with a sample of the potential users. The outcomes of such user studies, showed that participants considered that our approach delivers a more detailed knowledge about the city, and is more informative, when compared with the nor-mal sight-seeing visits in the city, performed by the same participants.